Need help from an expert?
The world’s top online tutoring provider trusted by students, parents, and schools globally.
To integrate cos^3(x), use the substitution u = sin(x) and the identity cos^2(x) = 1 - sin^2(x).
First, rewrite cos^3(x) as cos^2(x) * cos(x). Then, use the identity cos^2(x) = 1 - sin^2(x) to get:
cos^3(x) = cos^2(x) * cos(x) = (1 - sin^2(x)) * cos(x)
Next, substitute u = sin(x) and du/dx = cos(x) dx to get:
cos^3(x) dx = (1 - u^2) du
Now, integrate both sides with respect to u:
∫ cos^3(x) dx = ∫ (1 - u^2) du
= u - (1/3)u^3 + C
Substitute back in u = sin(x) to get the final answer:
∫ cos^3(x) dx = sin(x) - (1/3)sin^3(x) + C
Study and Practice for Free
Trusted by 100,000+ Students Worldwide
Achieve Top Grades in your Exams with our Free Resources.
Practice Questions, Study Notes, and Past Exam Papers for all Subjects!
The world’s top online tutoring provider trusted by students, parents, and schools globally.